The locker ate Lucy! - Chabert, Jack; Ricks, Sam (2014)
Only a week into his job as hall monitor and class protector, Sam Graves and his friends Lucy and Antonio are trying to uncover the secrets of Eerie Elementary, their living and malevolent school--and then Lucy gets eaten by her locker.
Appeals to 1st-3rd graders.
Reading level grade 2.
Keywords: Elementary schools -- Juvenile fiction; Best friends -- Juvenile fiction; Rescues -- Juvenile fiction; Horror tales; Schools -- Fiction; Best friends -- Fiction; Friendship -- Fiction; Rescues -- Fiction; Horror stories; Horror fiction